1996
DOI: 10.1029/96pa01858
|View full text |Cite
|
Sign up to set email alerts
|

Oceanic pH control on the boron isotopic composition of foraminifera: Evidence from culture experiments

Abstract: Culture experiments were carried out with the species Orbulina universa at four different pH values (7.70±0.05, 8.15±0.05, 8.60±0.05, and 9.00±0.10) in order to establish the pH‐dependence of boron isotope fractionation between seawater and foraminifera. A clear relationship between the boron isotopic composition of the foraminifera and the pH of the seawater culture solutions was found, showing heavier boron isotopic composition at higher pH. This finding supports the viability of boron isotopes as a paleo‐pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
211
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 205 publications
(235 citation statements)
references
References 11 publications
24
211
0
Order By: Relevance
“…Although the plankton tow results 21 are preliminary, they support the hypothesis that respiration and photosynthesis are the key physiological parameters 22 responsible for species-specific vital effects. , 1996Spivack et al, 1993). …”
Section: Abstract 11 12mentioning
confidence: 99%
“…Although the plankton tow results 21 are preliminary, they support the hypothesis that respiration and photosynthesis are the key physiological parameters 22 responsible for species-specific vital effects. , 1996Spivack et al, 1993). …”
Section: Abstract 11 12mentioning
confidence: 99%
“…Many studies have indicated that only B(OH) − 4 is incorporated preferentially into corals marine carbonates (Vengosh et al, 1991;Hemming and Hanson, 1992;Hemming et al, 1995;Spivack et al, 1993;Sanyal et al, 1996Sanyal et al, , 2000. Under this circumstance, all the δ 11 B values of carbonates are considered to be paralleled with the theoretical δ 11 B sw3 and are lower than that of the parent seawater; α carb−sw between carbonates and seawater are lower than 1 and increase with pH.…”
Section: Model 3: Both Chemical Reaction and Adsorption Of Boron Incomentioning
confidence: 98%
“…But when T r = 20 h, the maximum [B] d may appear at pH ≤ 9.5, while the highest value at pH 9.5 is 1859 ppm, which is much higher than 951.5 ppm at pH 10. Considering the slight difference in the (Sanyal et al, 1996). The variation trend of δ 11 B for T r = 0 h and T r = 20 h are basically same and all the δ 11 B d values are enriched in the heavy isotope relative to the δ 11 B fsw (Fig.…”
Section: The Partition Coefficient Of Boron Between Brucite and Finalmentioning
confidence: 99%
See 2 more Smart Citations